Effectiveness of Various Light Sensors for Indoor Use - Guntara, Diki; Sunardi, Sunardi (Signal and Image Processing Letters, 2025)
A light sensor is a type of electronic device that can produce changes in visible light energy or infrared light into electrical energy by utilizing the electrical current and resistance that enters the light sensor. This research objective is to design the light sensor circuit and program that can have a light sensor sensitivity to the light intensity in the room and test the success of indoor light sensors from the cheapest to the most expensive sensors. The sensors used are LDR, BH1750, and Photodiode. The research stage carried out was to prepare the equipment in a boarding room with dimensions of 3x3. The light intensity of windows and lamps for 10 days with three different sessions in the morning, afternoon, and evening are measured. Linear regression calibration is used to obtain more accurate results. The results of the light sensor used are compared with a digital lux meter. The cheapest sensor, namely the LDR, has the slowest response to light and is less accurate with an error value of 23.74%. An affordable sensor, namely a Photodiode sensor, has a fast response to light, but the results are less stable with an error value of 18.20%. The more expensive sensor is the BH1750 with the highest accuracy and stability with an error value of 7.53%.